Highly hydroxide conductive ionomers with fullerene functionalities. Issue 13 (14th January 2016) - Yang, Zhengjin; Liu, Yazhi; Guo, Rui; Hou, Jianqiu; Wu, Liang; Xu, Tongwen
Abstract : A novel ionomer was designed that will not poison the catalyst in alkaline fuel cells, by incorporating for the first time N -methyl pyrrolidine-C60 cation in polymeric anion exchange ionomers. Abstract : A novel ionomer was designed that will not poison the catalyst in alkaline fuel cells, by incorporating for the first time N -methyl pyrrolidine-C60 cation in polymeric anion exchange ionomers. The resultant fullerene-based anion exchange ionomer shows an extremely high hydroxide conductivity (182 mS cm −1 ) at a low cation concentration (0.62 mmol g −1 ).